¿Es posible detener la deforestación en la Amazonía peruana? - Dourojeanni, Marc J. (2022)
There are conservatively 9.6 million deforested hectares in the Peruvian Amazon. Out of them only 1.9 million support crops and livestock produced each year. The remaining ones, that is four hectares out of every five, is underused or abandoned and partly degraded. It is also known that each hectare in agricultural production produces one-third to one-half of what it could if well-known agricultural techniques were applied. However, deforestation continues at an increasing rate, with 190,000 ha of forests destroyed in 2020. Part of the problem is lack of technical and credit assistance for producers, as well as disorderly construction of roads that encourage deforestation. However, the main obstacle is that most of the deforestation is informal and occupies lands classified as suitable for forestry that cannot be granted as property by law and in which mid- and longterm investments are not made for that reason. Therefore, legalizing ownership of around seven million deforested hectares is proposed to stop deforestation. These are already occupied and it is technically, economically, and sustainably feasible to produce crops in them, applying proven strategies such as agroforestry, permanent crops, and reforestation.